Cross Model Access in the Multi-Lingual, Multi-Model Database Management System - Anastasopoulos, Achilles (1997)
Relational, hierarchical, network, functional, and object oriented databases support its corresponding query language, SQL, DL/I, CODASYL-DML, DAPLEX, and OO-DML, respectively. However, each database type may be accessed only by its own language. The goal of M2DBMS is to provide a heterogeneous environment in which any supported database is accessible by any supported query language. This is known as cross model access capability. In this thesis, relational to object oriented database cross model access is successfully implemented for a test database. Data from the object oriented database EWIROODB is accessed and retrieved, using an SQL query from the relational database EWIROODB. One problem is that the two interfaces (object oriented and relational) create catalog files with different formation, which makes the cross model access impossible, initially. In this thesis the relational created catalog file is used, and the cross model access capability is achieved. The object oriented catalog file must be identical with the relational one. Therefore, work yet to be done is to write a program that automatically reformats the object oriented catalog file into an equivalent relational catalog file.